Health needs of refugee children identified on arrival in reception countries: a systematic review and meta-analysis. Issue 1 (11th September 2019) - Baauw, Albertine; Kist-van Holthe, Joana; Slattery, Bridget; Heymans, Martijn; Chinapaw, Mai; van Goudoever, Hans
Abstract : Background: The worldwide number of refugees has considerably increased due to ongoing wars, national instability, political persecution and food insecurity. In Europe, about one-third of all refugees are children, an increasing number of which are travelling alone. There are often no systematic medical health assessments for these refugee children on entry in reception countries despite the fact that they are recognised as an at-risk population due to increased burden of physical and mental health conditions. We aimed to perform a systematic review of the literature to describe the health status of refugee children on entering reception countries. Methods: A systematic search of published literature was conducted using the terms refugee, immigrant or migrant, medical or health, and screening. Results: Of the 3487 potentially relevant papers, 53 population-based studies were included in this review. This systematic review showed that refugee children exhibit high estimated prevalence rates for anaemia (14%), haemoglobinopathies (4%), chronic hepatitis B (3%), latent tuberculosis infection (11%) and vitamin D deficiency (45%) on entry in reception countries. Approximately one-third of refugee children had intestinal infection. Nutritional problems ranged from wasting and stunting to obesity. Conclusions: Refugee children entering reception countries should receive comprehensive health assessments based on the outcomes of this systematic review, national budgets, cost-effectiveness and personal factors of the refugees. The health assessment should be tailored to individual child health needs depending on preflight, flight and postarrival conditions. A paradigm shift that places focus on child health and development will help this vulnerable group of children integrate into their new environments. PROSPERO registration number 122561.